Encounters in the Victorian Press
XIV, 268 p. 10 illus.
Keywords: Encounters in the Victorian Periodical Press focuses on the unique characteristic of the Victorian periodical press - its development of encounters between and among readers, editors, and authors. Encounters promoted dialogue among diverse publics, differing by class, gender, professional and political interests, and ethnicity. Through encounters, the press emerged to become a central public space for debates about society, politics, culture, public order, and foreign and imperial affairs. This book captures the richness of these interactions and a variety of voices and opinions.